A Philosophical Expose Towards A ‘God After God’ - Onah, Gregory Ajima; Ogar, Thomas Eneji; Okoi, Ibiang O. (International Journal of Indonesian Philosophy & Theology, 2023)
The escalation of violent incidents in recent times has brought religions to the forefront of world politics, resulting in a shift from their traditional role as conduits of divine revelation to becoming instruments of power and dominance. This phenomenon of kratophany exemplifies the manifestation of violence within religious contexts. The occurrence of violence may be attributed to the foundation of eschatological interpretations within various theological frameworks. The emergence of religious triumphalism and fundamentalism stemming from these theological perspectives has posed a significant danger to both world peace and ecumenical dialogue. The need for peace among faiths has transitioned from being a mere choice to an urgent necessity in contemporary times. The deity that is sought to be understood via the lens of eschatology is a divine being that exists in the future, sometimes referred to as an "after God." Hence, in order to get this comprehension, it is imperative to relinquish any remnants of onto-theological thought that now plague the eschatological analysis of religions. The violent interpretations of eschatologies used by Abrahamic faiths result in a significant loss of significance. The present research aims to address the hermeneutic context that poses a threat of religious violence. This intervention might be likened to Abraham getting Isaac back after first renouncing the notion of a violent sacrifice. In the present day, it is imperative for the Abrahamic faiths to discontinue the practise of harsh sacrifice and instead embrace the concept of peace as a valuable offering.